IMPLEMENTASI PROGRAM BERAS MISKIN (RASKIN) DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT RUMAH TANGGA MISKIN DESA MONTOR KECAMATAN BANYUATES KABUPATEN SAMPANG - Cahyono, Anjar (JPAP: Jurnal Penelitian Administrasi Publik, 2015)
The purpose of this study to determine Raskin Program Implementation in the village ofthe District Montor Banyuates Sampang, seen from the implementation process, namelyHow Poor Rice Program and Factors of success and failure in the implementation ofRaskin. Data analysis technique used is Data Reduction Based on the results of thisresearch is that the implementation of Raskin in the village of the District MontorBanyuates not run according to the rules It can be known First, regarding any number ofrice distributed, second often incompatible with what was programmed by government,the price of which is not in accordance with the initial planning, the quality of rice uglyFourth, fifth discrepancies raskin prices in 2015, the Sixth of a delay in thedisbursement of Raskin of area is not deposited to Bulog. Factors of success and failureseen from the communication that exists is not good because it was done quickly andthe lack of time for the executive to conduct socialization program, Executive managerof Raskin in the village Montor poorly for full implementation Rice Miskin,implementor at village Montor less prudent in implementing the program Raskin so thatthe distribution of rice Poor (Raskin) is not effective and not well targeted, and Societyin the receiving Raskin mostly unaware of the institution / organization what poor ricewas issued, in the implementation of Raskin Community, the main target of theprogram, it is expected that in every implementation kegiatanya rice for the poorprogram (Raskin) in the village of the District Montor there Banyuates control orsupervision by local authorities to prevent irregularities in the distribution of rice.Keyword : mplementation, Program Beras Miskin, Public Welfare, Sampang